Organophosphate intoxication in 2 dogs from ingestion of cattle ear tags. Issue 4 (30th June 2019) - Asokan, Vibha R.; Kerl, Marie E.; Evans, Tim; Harmon, Meghan
Abstract: Objective: To describe 2 cases of organophosphate intoxication through a previously unreported method of exposure. Case series: A 2‐year‐old intact male Australian Cattle Dog (case 1) presented with progressive muscarinic and nicotinic clinical signs, and a 3‐year‐old neutered male mixed breed dog (case 2) presented after known ingestion of cattle ear tags. The dog in case 1 was discovered to have ingested cattle ear tags after abdominal radiographs. Organophosphate testing of gastric contents confirmed diazinon toxicosis. The dog in case 2 was found to be eating ear tags by the owner. The tags in case 2 contained diazinon and coumaphos. The dog in case 1 was treated with gastric lavage, gastroprotectants, prokinetics, antiemetics, pralidoxime chloride, and atropine. The dog in case 2 was treated with pralidoxime chloride. Both patients received standard supportive and nursing care and recovered completely with no further concerns. New or unique information provided: This is a novel exposure to organophosphates that has not been reported in small animals. In dogs with relevant clinical signs and potential environmental exposure, cattle ear tag ingestion is an important differential diagnosis to consider.